Inherently safer facility layout with multiple floors (2018)
In a process plant, operation and safety factors are affected by the positioning of equipment among space. As mathematical and optimization methods have started to aid expert criterion for layout distribution, interest has been drawn towards efficient formulations and methods which include uncertainty treatment and risk assessment tools in both objective functions and constraints. The current work proposes a MINLP formulation for a 3D facility layout problem based on a multi-floor approach, which accounts for both operation and safety aspects. The Safety Weighted Hazard Index designed by Khan, Husain, and Abbasi is used to measure these aspects. A metaheuristic algorithm known as Bacterial Foraging Optimization (BFO) algorithm solves the problem. The proposed methodology is applied to a facility example case used in the literature to evaluate the effectiveness and efficiency of the current approach.